2014
DOI: 10.1039/c4lc00910j
|View full text |Cite
|
Sign up to set email alerts
|

The pumping lid: investigating multi-material 3D printing for equipment-free, programmable generation of positive and negative pressures for microfluidic applications

Abstract: Equipment-free pumping is a challenging problem and an active area of research in microfluidics, with applications for both laboratory and limited-resource settings. This paper describes the pumping lid method, a strategy to achieve equipment-free pumping by controlled generation of pressure. Pressure was generated using portable, lightweight, and disposable parts that can be integrated with existing microfluidic devices to simplify workflow and eliminate the need for pumping equipment. The development of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
89
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 45 publications
0
89
0
3
Order By: Relevance
“…This solution uses 150 µL disposable syringes to inject 25 µL urine into a PDMS detection cell containing the reagents for fluorescence detection using the phone camera interfaced with a reusable instrument (Figure 2d). The use of a syringe is a practical choice in this case, but one can imagine a lid pump (Begolo et al, 2014) operating as a suction device integrated with the rest of the fluidics, which could additionally provide precise volume metering. ULOC finger pumps are simpler (Comina et al, 2015a), but they still have not been demonstrated for suction.…”
Section: Sample Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…This solution uses 150 µL disposable syringes to inject 25 µL urine into a PDMS detection cell containing the reagents for fluorescence detection using the phone camera interfaced with a reusable instrument (Figure 2d). The use of a syringe is a practical choice in this case, but one can imagine a lid pump (Begolo et al, 2014) operating as a suction device integrated with the rest of the fluidics, which could additionally provide precise volume metering. ULOC finger pumps are simpler (Comina et al, 2015a), but they still have not been demonstrated for suction.…”
Section: Sample Extractionmentioning
confidence: 99%
“…As an alternative to confined vacuum, the use of finger pumps (Comina et al, 2015a;Begolo et al, 2014;Iwai et al, 2014) could be an option to simplify this kind of extraction elements. The concept described by Begolo et al, 2014, is a 3D printed lid configured as a pump to generate positive and also negative pressure (Figure 2b).…”
Section: Sample Extractionmentioning
confidence: 99%
See 3 more Smart Citations